(3QSGdI aj GdTcd (B[(3GdedbH(B] (3HGdbWGYs - (3GdSLRj , CMeO Hf eMeO Hf YHO GdLdjd, CHh SYjO,J (B477 (3g` s ((3GdehUd s)
(3ChdgG (B:s
(3YeQ Gddg ehGWf GdMceI , hSgd dc WQb GdCUGHI bO cfJ CjOc Gddg SCdJfi efP Mjf EfTGA ebGdI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B276(3X (B- (3U(B280(3hs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B115s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B388 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B50 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdQjGVjGJs